UNVEILING THE CATALIST: : HOW POKDARWIS SHAPES TOURISM PRODUCT DEVELOPMENT IN TINGKIR LOR, SALATIGA - Lasso, Aldi; Wardana, Abednego Dwika; Saweho, Joy Bezaleed (SABBHATÃ YATRA : Jurnal Pariwisata dan Budaya, 2024)
Tourism product development tends to focus on physical aspects and improvements to attractions. However, the pivotal element of human resources in product development is often overlooked. Based on a qualitative approach, this study provides a case analysis highlighting the important roles of Pokdarwis in Tingkir Lor Tourism Village, as the local destination management organization, contributing to the sustainability of the tourism village amidst turbulent situations. Data were collected through interviews, observations, and document studies. The results demonstrate that Pokdarwis Svarna Gatra plays vital roles in the success of tourism product development in Tingkir Lor. It is evident that human resources are integral to the tourism product development process. Regardless of the quality of physical attractions, sustainable tourism product development hinges on the availability of adequate human resources.